Evaluation of Heat Resistance Adequacy and Non Combustible Materials Construction of a Multifunctional Building - Murali .P, Lilly Grace; Sampathkumar, V. (Civil Engineering Journal, 2018)
Fire in buildings is one of the major threats. This threat is increasing day by day. This problem necessitates the building designers, construction professionals and the fire professional to find the solution. A detailed study with analysis requires towards the existing fire safety measures. This study analysis results will reveals the adequacy of existing measures. In this article one of the multifunctional building is selected as research sample. In this building applied research type is adopted. Case study method is used to study the each component of the building. The planning parameters of the building and the designing of the structural position are observed in depth manner. The non-combustible materials are identified in the construction of the building. The heat resistance adequacy of each components of the building is evaluated with respect to codel recommendations. The basic concept of fire and life safety measures in buildings are common in international, national and the regional level. These recommendations are thoroughly applied in this research work. These works are analyses and the results or findings are derived. These results are summed up and explained about its objectives. The paper is concluded with comprehensive fire safety measures applications in buildings and recommends fire related various factors research in future. The ultimate aim of this article work is to safe guard lives and property in buildings.